Cytokine and Chemokine Profiling in Patients with Hand, Foot and Mouth Disease in Singapore and Malaysia - Teo, F.M.S.; Nyo, M.; Wong, A.A.; Tan, N.W.H.; Koh, M.T.; Chan, Y.F.; Chong, C.Y.; Chu, J.J.H. (Nature Publishing Group, 2018)
Hand, foot and mouth disease (HFMD) is a prevalent contagious childhood disease typically associated with fever, oral lesions and limb exanthema. While HFMD is caused by a plethora of serotypes of viruses under the genus Enterovirus within the Picornaviridae family, Coxsackievirus A16 (CV-A16) and Enterovirus 71 (EV-A71) are considered the main etiological agents. In recent years however, other viruses have also been isolated in considerable numbers from infected individuals in many regions, joining the legion commonly associated with HFMD. The present study investigated the cytokine and chemokine profiles of HFMD patients from Singapore and Malaysia for the first time. Comparative cohort studies of EV-A71-associated HFMD cases revealed that the Malaysia cohort had a distinct profile from the Singapore cohort, and this could be partly attributed by different EV-A71 genotypes. As the isolation of CV-A6, instead of CV-A16, had become prevalent in the Singapore cohort, it was also of particular interest to study the differential cytokine and chemokine profiles. Our data revealed that overlapping as well as unique profiles exist between the two major causative clinical isolates in the Singapore cohort. Having a better understanding of the respective immunological profiles could be useful for more accurate HFMD diagnosis, which is imperative for disease transmission control until multi-valent vaccines and/or broad-spectrum anti-viral drugs become available.